Fundamentals of educational research and data analysis : a PAFTE textbook development project - Padua, Roberto N.; Santos, Rosita G. (Quezon City, Philippines : Katha Publishing Co, Inc., 1998)
This book attempt to show the strong connection between the two subjects. his is not an " applies arithmetic" book. it does not deal with computation nor formulae.
Chapter: Overview of educational research -- Chapter 2: Formulating the research problem -- Chapter 3:The literature of related literature and studies -- Chapter 4: Method of research -- Chapter 5: Instrument for data collection -- The analysis of variance -- Chapter: 7 The regression model -- Chapter 8: Analysis of covariate models and experimental designs.
Includes bibliographical references.
Keywords: RESEARCH METHODS